SG_C-Projective, Injective and Flat modules - Parimala M; Udhayakumar Ramalingam (IndoMS, 2019)
In this paper we introduce the concepts of SG_C-projective, injective and flat modules, where C is a semidualizing module and we discuss some connections among SG_C-projective, injective and flat modules.